An Economic Analysis of Giant Freshwater Prawn Pond Culture in Thailand - Kantangkul, Piti (1987)
Productivity of Giant Freshwater Prawn (GFWP) pond culture in Thailand is considered to be relatively low compared to its potential productivity which leads to high per uni t cost of production. One measure by which productivity and profit can be raised is to make an adjustment of resource use in cases where the resources are used inefficiently. If the resources use are price efficient, another way to raise their productivity is to increase their technical efficiency. This study explores the issue of relative economic efficiency (technical coupled with price efficiency) among small, medium, and large farms; between farms with and without juveniles nursery practices (JNP and non-JNP)i and between farms facing diseases and/or water pollution (DWP) and farms facing none (non-DWP) within the framework of normalized restricted profit function. This was accomplished by statistically testing various hypotheses from the joint estimation of the normalized restricted profit function and four factor share equations. Further, production elasticities, output supply and input demands elasticities were subsequently derived from these estimators. The normalized restricted profit was specified as a function of four normalized prices of variable inputs (juveniles, feeds, labour and fuel), two quantities of fixed inputs (farm asset and pond area), experience and four dummy variables to categorize the three different farm sizes, two juveniles practices (JNP and non-JNP farms) and two natural conditions (DWP and non-DWP farms). The results of this study indicate that the variable inputs use in GFWP pond culture was price efficient and constant returns to scale existed in this type of farming. Medium farms were found to attain the highest economic efficiency followed by small and large farms while JNP and non-DWP farms obtained higher economic efficiency than those non-JNP and DWP farms. The existence of differences in economic efficiency among groups of farms was due to their differences in technical efficiency. The productivity and profit of GFWP pond culture can be increased through improving the technical efficiency of this farming. It i s recommended that operating GFWP pond culture within medium scale farming with juveniles nursery together with proper water management, disease prevention and treatment should be encouraged.